Emphasis on the composition of speech form of reasoning and the text of reasoning as a problem of modern linguistic (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
The article discusses the factors that influenced the formation of text of reasoning and its specific modifications. Logic-structural peculiaritys of reasoning texts composition being analyzed and delineated their main text-forming parameters. Text typology problem on the level of speech composition being investigated, taking into account lingvo-stylistical factors.The essays of the second half of the XVII century being examined as an intermediate genre that occurs at the intersection of literature, journalism and philosophy. This period is characterized by the formation of English literature national language norms, when philosophical, lyrical, emotional, intellectual understanding of life changes took place and the battle in the literature over the new style, designed the dynamics of the inner life of the man has begun. Being investigated the stylistic influence and sings of the new style in connection with principal literary direction of epoch-classicism. Attention is drawn to rational-logical direction of style. Special attention is paid to small epic forms (essays, meditations, diaries), specific language which is dictated by the general structural peculiarities of this prose, strictly rational-logically and rhetorically organized.The reference to the analysis of the text of the second half of the XVII century is not accidental. This period was defined by researchers as “experimental” in the development of modern English prose. The variety of later developed verbal forms of prose was most vigorously pioneered precisely in this century. The text of reasoning is considered as a whole-formed, structural and communicative unity created on the basic of the compositional – speech form, the elements of which reproduce the speech process as the process of the work of consciousness. The revival of the rhetoric in the XVII century also determined the special nature of the generation of text in which lexico-sematic and synthetic levels were subjected to compulsory organization. The element of consciousness and correctness is obvious here, so the structure appears naked. The reasoning here is not contaminated with other compositional speech forms, but represents the whole speech production. The basis for the proposed classification of English prose texts of second half of the XVII century in not genre-based features, but a type of compositional-speech form. The typological features of the speech structure of text-reasoning are studied.
Keywords: texts reflections; composition; typology; essays; logical-structural features